Research on secure routing algorithm in satellite networks - LI Zhe; LIU Jun (Tongxin xuebao)
The key technologies in satellite networks security were researched.A security routing algorithm was proposed.By static configuration combining together with dynamic adjustment,the algorithm realized dynamic routing.Based on the credence model,the security mechanism was added.When it found there was malicious behavior in the network,it would react actively.It effectively guaranteed the security of satellite networks and protectd the network from kinds of attacks.